2007
DOI: 10.1111/j.1537-2995.2007.01104.x
|View full text |Cite
|
Sign up to set email alerts
|

Human cord blood CD133+ cells immunoselected by a clinical‐grade apparatus differentiate in vitro into endothelial‐ and cardiomyocyte‐like cells

Abstract: The appearance of both endothelial- and cardiomyocyte-like cells from parallel cultures of frozen-thawed-immunoselected UCB CD133+ cells by a clinical-grade method and previously reported data on lack of major signs of rejection of these cells in immunocompetent rats subjected to experimental liver damage suggest a possible role of these allogeneic HSCs in cell therapies designed for regenerative treatments of ischemic diseases of human myocardium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 21 publications
0
36
0
Order By: Relevance
“…1B, 1C). Of interest, Comb 4 exhibited greater EPC-CFU productivity, especially in DEPC-CFU, compared with the previously reported Comb 1 (SCF, Flt-3 ligand, IL-3, IL-6) for EPC expansion [5,40]. Collectively, we determined that the Comb 4 growth factors are the most effective culture system for vasculogenic colony-forming EPC expansion, and we named them the QQc control system.…”
Section: Clinical Significance Of the Serum-free Quality And Quantitymentioning
confidence: 86%
See 3 more Smart Citations
“…1B, 1C). Of interest, Comb 4 exhibited greater EPC-CFU productivity, especially in DEPC-CFU, compared with the previously reported Comb 1 (SCF, Flt-3 ligand, IL-3, IL-6) for EPC expansion [5,40]. Collectively, we determined that the Comb 4 growth factors are the most effective culture system for vasculogenic colony-forming EPC expansion, and we named them the QQc control system.…”
Section: Clinical Significance Of the Serum-free Quality And Quantitymentioning
confidence: 86%
“…Park et al reported that CB-CD133 ϩ cells cocultured with rat CMCs after pretreatment with platelet-derived growth factor and epidermal growth factor feature cardiomyocytic phenotypes in terms of morphology and expression of lineage-specific markers [48]. Bonanno et al [40] also demonstrated that a specific differentiation culture system after preconditioning of CB-CD133 ϩ cells with SCF, Flt-3 ligand, IL-3, and IL-6 for 2 days promoted differentiation into EC or CMC lineages in vitro.…”
Section: Enhanced Cardiac Repair By Engraftment Of Post-qqc Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many latest researches carried out with in vitro or ex vivo differentiated ES cells, fetal and umbilical cord blood (UCB)-derived stem cells and their functional progeny as well as adult stem/progenitor cells have provided accruing substantiation sustaining their potential therapeutic application for numerous genetic and degenerative disorders (3,4,14,22,(26)(27)(28)(29)(30)(31)(32)(33). Allogenic transplantation of stem cells or their additional differentiated progeny into patients may markedly represent a potential therapeutic approach, unaccompanied or in combination with the predictable treatments, for conquering the progressive failure of functions of adult stem cells with aging and degenerative diseases (14,34).…”
Section: Stem Cell Based-therapies In Regenerative Medicinementioning
confidence: 99%